Synbiotic Structured Education (Probiotics and Prebiotics) in order to increase the community's resistance to the spread of Covid-19 - Endro Tri Susdarwono (UNIB Press, 2022)
This study aims to provide an overview of community service carried out in the form of Synbiotic Structured Education (Probiotics and Prebiotics). The data analysis method uses a statistical test of hypothesis testing on changes in the Mac Nemar change test to ascertain whether or not there is a change in the behavior of the object of research. In this method, the change in state or response shown by the object is analyzed with the help of a table called a 2 x 2 frequency table. The table is used as a tool because this method is applied to 2 groups of paired samples. The conclusion of community service that has been carried out in the form of structured education of synbiotics (probiotics and prebiotics) in order to increase the community's resistance to the spread of COVID-19 is able to make changes in behavior by the community in general and families in particular in applying the use of synbiotics to increase the body's resistance to enteric cases. acute and respiratory infections.